Problem of Fulfilling Children's Rights After Divorce: A Study of the Causative Factors and Their Legal Implications - Mauliddin (Journal of Family and Sharia, 2026)
Divorce does not remove the obligations of parents in fulfilling the rights of children, but in practice the fulfillment of these rights is still often neglected. Children often do not get the right to maintenance, upbringing, education, health, and affection due to various factors, such as economic limitations, low legal awareness, prolonged conflicts between parents, weak implementation of court decisions, and lack of optimal supervision of the implementation of parental obligations. This study aims to analyze the factors that cause the non-fulfillment of children's rights after divorce and their legal implications in the perspective of Islamic law and positive law in Indonesia. This research is a normative legal research with legislative, conceptual, and case approaches. Legal materials are obtained from laws and regulations, court decisions, books, and scientific articles. The results of the study show that the main factors causing the non-fulfillment of children's rights include economic factors, low compliance with court decisions, conflicts between parents, weak child support execution mechanisms, and lack of state supervision. This condition has an impact on the protection of children's rights and the application of the principle of the best interests for children. Therefore, it is necessary to strengthen regulations, the effectiveness of the implementation of court decisions, and synergy between the state, judicial institutions, and the community to ensure the fulfillment of children's rights after divorce.